An Overview of the Development of Flexible Sensors. Issue 33 (3rd July 2017) - Han, Su‐Ting; Peng, Haiyan; Sun, Qijun; Venkatesh, Shishir; Chung, Kam‐Sing; Lau, Siu Chuen; Zhou, Ye; Roy, V. A. L.
Abstract : Flexible sensors that efficiently detect various stimuli relevant to specific environmental or biological species have been extensively studied due to their great potential for the Internet of Things and wearable electronics applications. The application of flexible and stretchable electronics to device‐engineering technologies has enabled the fabrication of slender, lightweight, stretchable, and foldable sensors. Here, recent studies on flexible sensors for biological analytes, ions, light, and pH are outlined. In addition, contemporary studies on device structure, materials, and fabrication methods for flexible sensors are discussed, and a market overview is provided. The conclusion presents challenges and perspectives in this field. Abstract : Flexible sensors have been extensively studied due to their great potential for Internet of Things and wearable electronics applications. Recent studies on flexible sensors for biological analytes, ions, light, and pH are outlined. Contemporary studies on device structure, materials, fabrication methods, and a market overview for flexible sensors are discussed. In conclusion, challenges and perspectives in this field are presented.